Activated carbon-Polyaniline composite active material slurry electrode for high capacitance, improved rheological performance electrochemical flow capacitor. (10th September 2020) - Singh, Pushpendra; Pal, Kaushik
Abstract: Conducting polymer polyaniline (PANI) offers very high capacitance but suffers from poor cycling stability. On the other hand, electrochemical flow capacitor (EFC) systems allow replacement of electrode slurry materials whenever needed. Thus using polyaniline as active material in slurry for EFC system can enhance the performance of suspension electrode, and the flow system can itself resolve the issue of poor cyclic stability of polyaniline by replacing it with new fresh slurry whenever it decomposes. However, pristine polyaniline slurry in the flow system is highly prone to decomposition. Hence an activated carbon-polyaniline (AC-PANI) composite active material has been prepared. The porous structure of activated carbon (AC) helps in holding polymer chains upon successive cycling. AC-PANI composite in slurry results in improved capacitive performance 173.8 F- g −1 (139.04 C- g −1 ) @ 2 mV- s −1 during static slurry testing. After 200 cycles @ 20 mV- s −1, the AC-PANI composite slurry holds 91% capacitance. In the flow test, the composite slurry demonstrates 48% improvement in volumetric capacitance as compared to pristine AC slurry. In addition to this, AC-PANI composite slurry exhibits a gravimetric energy density of 15.46 Wh-kg −1 in static slurry testing mode and a volumetric energy density of 0.43 Wh- L −1 during the intermittent flow test. Moreover, AC-PANI composite slurry also has lower viscosity comparative to pristine AC slurry under the same mass loading. In this way, this AC-PANI composite enjoys the benefit of improved capacitive performance with better rheological behavior for suspension electrode. Graphical abstract: Image, graphical abstract